2006
DOI: 10.1007/s10964-005-9010-9
|View full text |Cite
|
Sign up to set email alerts
|

The Skinny on Body Dissatisfaction: A Longitudinal Study of Adolescent Girls and Boys

Abstract: The present study tested whether theoretically derived risk factors predicted increases in body dissatisfaction and whether gender moderated these relations with data from a longitudinal study of 428 adolescent girls and boys because few prospective studies have examined these aims, despite evidence that body dissatisfaction increases risk for various psychiatric disturbances. Body dissatisfaction showed significant increases for girls and significant decreases for boys during early adolescence. For both gende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
334
5
37

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 430 publications
(420 citation statements)
references
References 62 publications
29
334
5
37
Order By: Relevance
“…It is also apparent in a later study by this group. Here, perceived low social support by parents, and to a lesser extent by peers, was shown to predict body dissatisfaction (Bearman et al 2006); the effect being weak. Participants were younger adolescents (mean 13 .…”
Section: Social Support and Social Contagionmentioning
confidence: 80%
“…It is also apparent in a later study by this group. Here, perceived low social support by parents, and to a lesser extent by peers, was shown to predict body dissatisfaction (Bearman et al 2006); the effect being weak. Participants were younger adolescents (mean 13 .…”
Section: Social Support and Social Contagionmentioning
confidence: 80%
“…Social media use is particularly popular among young women (Kimbrough, Guadagno, Muscanell, & Dill, 2013;Muscanell & Guadagno, 2012), a demographic for which body dissatisfaction (i.e., dissatisfaction with one's current physical self) is also particularly problematic (Bearman, Martinez, Stice, & Presnell, 2006;Ricciardelli & McCabe, 2001). Existing research has demonstrated a positive correlation between Facebook usage and body dissatisfaction (Fardouly & Vartanian, 2015;Tiggemann & Miller, 2010;Tiggemann & Slater, 2013, 2014, but there is currently no theoretically-driven experimental research examining Facebook's impact on young women's body image concerns.…”
Section: The Effect Of Facebook On Body Image and Mood 3 Social Compamentioning
confidence: 99%
“…Internalizing problems, particularly negative affect, have been shown to be predictive of BN and body image dissatisfaction (Bearman et al, 2006;Leon, Fulkerson, Perry, Keel, & Klump, 1998). Disruptive problems such as impulsive substance use (Leon et al, 1998) and self-reported aggressive behavior (Killen et al, 1994) have been linked with BN.…”
Section: Theoretical Rationalementioning
confidence: 99%